Analisis Kepuasan Konsumen Terhadap Pemasaran Online Cake Pisang Lampung Banana Foster Melalui E-Commerce Pada Masa Pandemi Covid-19 Cabang Bandar Lampung - Muhammad Revvy Kurniawan; Aring Hepiana Lestari, Dyah; Marlina, Lina (Journal of Food System & Agribusiness, 2023)
The research aims to analyze the type of e-commerce, consumer satisfaction levels, and e-services performance used in the online marketing of banana foster banana cake. The research was done using a survey method on three banana foster lampung outlets in lampung town. There were 76 respondents who were selected through purposive sampling. Data collection took place in April - May 2021. Analysis methods used descriptive analysis, Customer satisfaction Index (CSI) analysis, and importance performance analysis (IPA). Research result shows that the media e-commerce, which banana foster often used for marketing and accessing information, is instagram because of good photo quality has its charm to display, the more obvious and uptodate information,, while for sending deliveries using gosend and grabexpress services. CSI score obtained was 86.87 % which means the consumer is very satisfied with online marketing through e-commerce. According to IPA analysis, banana foster has to improve the attribute for giving a faster response to consumer questions and helping customers who have difficulty doing online transactions.